Game-Based Learning in Interior Architecture Education - Babacan Çörekci, Tuğçe (Design and Technology Education: An International Journal, 2023)
The concept of play supports the experiential and creative aspects of the design field because it is a familiar and fun phenomenon and involves interaction. The use of game-based learning in design processes will increase participation by supporting the regulation of these processes and the problematic aspects of the design studio course, which is at the heart of design education. For this reason, this study investigates the use of game-based learning methods in the design studio processes, one of the most important courses in interior architecture education. The study, which preferred the embedded theory method to develop hypotheses, one of the qualitative research methods, investigated the effects of game-based learning on the understanding of design processes and time management in a voluntary workshop with second-year students of interior architecture faculty. The study preferred a pre-test-post-test design for a single group as the data collection instrument and was supported by observations. Consistent with this preference, data collected with participants prior to the workshop were analysed and the workshop structure was created, and an attempt was made to compare the results of the game-based learning method with the post-workshop observations and survey results.